2012
DOI: 10.1029/2012gc004189
|View full text |Cite
|
Sign up to set email alerts
|

Mantle dynamics beneath the Pacific Northwest and the generation of voluminous back‐arc volcanism

Abstract: [1] The Pacific Northwest (PNW) has a complex tectonic history and over the past $17 Ma has played host to several major episodes of intraplate volcanism. These events include the Steens/Columbia River flood basalts (CRB) and the striking spatiotemporal trends of the Yellowstone/Snake River Plain (Y/SRP) and High Lava Plains (HLP) regions. Several different models have been proposed to explain these features, which variously invoke the putative Yellowstone plume, rollback and steepening of the Cascadia slab, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 132 publications
(252 reference statements)
5
62
0
Order By: Relevance
“…This indicates that the parental basaltic magmas to this system might be changing through time, toward hotter basaltic magmas and greater degrees of partial melting of the mantle, a changing asthenospheric source composition or interaction with a more depleted mantle lithosphere [cf., Carlson and Hart, 1987]. Modeling of thermal anomalies using trench rollback and extension in the backarc also indicates that mantle temperatures should increase over time [Long et al, 2012]. In our model, slab rollback, back-arc extension, and the progressive steepening of the slab to the north results in enhanced counterflow ( Figure 7) and a plume in not a necessary heat source.…”
Section: Subsidence Of the Hlp And Effects On Rhyolite Outcrop Distrimentioning
confidence: 68%
See 3 more Smart Citations
“…This indicates that the parental basaltic magmas to this system might be changing through time, toward hotter basaltic magmas and greater degrees of partial melting of the mantle, a changing asthenospheric source composition or interaction with a more depleted mantle lithosphere [cf., Carlson and Hart, 1987]. Modeling of thermal anomalies using trench rollback and extension in the backarc also indicates that mantle temperatures should increase over time [Long et al, 2012]. In our model, slab rollback, back-arc extension, and the progressive steepening of the slab to the north results in enhanced counterflow ( Figure 7) and a plume in not a necessary heat source.…”
Section: Subsidence Of the Hlp And Effects On Rhyolite Outcrop Distrimentioning
confidence: 68%
“…Other workers using three-dimensional strain modeling [Druken et al, 2011;Long et al, 2012] have recently shown that the downdip only motion (Figure 7) on the Cascadia slab is insufficient to create the mantle wedge flow observed under Oregon and thus a combination of trench rollback, slab steepening, and back-arc extension is required to produce the seismic anisotropy observed. Downdip motion alone only produces weak corner flow and little upwelling from the mantle.…”
Section: Subsidence Of the Hlp And Effects On Rhyolite Outcrop Distrimentioning
confidence: 99%
See 2 more Smart Citations
“…The ~ 300 x 600-km, roughly oval flood basalt does not reflect the geometry of the magma source, but the topography of the land at the time of eruption (Christiansen et al, 2002); 4. The geochemistry of the CRB corresponds to shallow adiabatic decompression melting of mantle lithosphere, and the depths and temperatures of melting correspond to ~100 km and normal mantle temperatures near the base of the crust (e.g., Long et al, 2012). Mountain and other main CRB eruptive fissures, and 400 km south of the largest eruptive centers (Camp, 2013;Pierce et al, 2002).…”
Section: Frameworkmentioning
confidence: 99%